Safety, tolerability, pharmacokinetics, and pharmacodynamics of single and multiple doses of aficamten in healthy Chinese participants: a randomized, double-blind, placebo-controlled, phase 1 study - Zhao, Xue; Liu, Hongzhong; Tian, Wei; Fang, Ligang; Yu, Mengyang; Wu, Xiaofei; Liu, Aijing; Wan, Ruijie; Li, Li; Luo, Jinghui; Li, Yuqiong; Liu, Bo; et al. (Frontiers in Pharmacology, 2023)
Objectives: Aficamten is a selective, small-molecule allosteric inhibitor of cardiac sarcomere being developed as a chronic oral treatment for patients with symptomatic obstructive hypertrophic cardiomyopathy. This was the first-in-Chinese study aiming to investigate the safety, tolerability, pharmacokinetics, and pharmacodynamics of aficamten in healthy adults. Methods: This double-blind, randomized, placebo-controlled, phase 1 study was conducted in 28 healthy male and female Chinese participants after single ascending dose (SAD) and multi-dose (MD) administrations of aficamten. In the SAD cohort, 16 participants were randomized to receive a single oral dose of aficamten: 10 mg, 20 mg, or placebo. In the MD cohort, 12 participants were randomized to receive multiple doses of aficamten: 5 mg or placebo once daily for 14 days. Safety was monitored throughout the study with electrocardiograms, echocardiograms, clinical laboratory tests, and reporting of adverse events (AEs). Pharmacokinetic profiles of aficamten and metabolites, as well as CYP2D6 genetic impact, were evaluated. Results: A total of 35 treatment-emergent AEs were reported by 14 (50%) participants with mild severity. There were no serious AEs or adverse decreases in left ventricular ejection fraction below 50% during the study. Aficamten was dose-proportional over the dose range of 5–20 mg and accumulated in the MD cohort. Conclusion: Aficamten was safe and well-tolerated in the healthy Chinese adult participants. The pharmacokinetics of aficamten in the Chinese population was comparable to those previously found in Western participants. These phase 1 data support the progression of aficamten into future clinical studies in Chinese patients. Clinical Trial registration:https://clinicaltrials.gov, identifier: NCT04783766.